PENGARUH MODEL THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMA NEGERI 14 PADANG - Novitasari, Amanda; Domi Fella Henanggil, Mita; Amir, Amril; Afnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of negotiation text writing skills among tenth-grade students at SMA Negeri 14 Padang. The purpose of this study was to describe the effect of the “think-pair-share” model on the negotiation text writing skills of tenth-grade students at SMA Negeri 14 Padang. This study employed a quantitative approach using an experimental method and a posttest-only control group design. The research sample consisted of 40 tenth-grade students. Class X.E5 served as the experimental class and class X.E3 as the control class, both selected using purposive sampling. Research data were collected through a performance test on negotiation text writing and analyzed using descriptive and inferential statistics. The results showed that students’ negotiation text writing skills improved after the Think-Pair-Share model was implemented. The average score of the experimental class was higher than that of the control class, and the results of the hypothesis testing showed that the use of the Think Pair Share model had a significant effect on students’ negotiation text writing skills. Thus, the Think Pair Share model proved to be effective in improving the negotiation text writing skills of tenth-grade students at SMA Negeri 14 Padang.